Clostridium tertium bacteremia and hepatic abscess in a non-neutropenic patient. (2019) - Milano, Victoria; Biehle, Lauren; Patel, Shalvi; Hammer, John
Abstract: A 43-year-old previously healthy man presented with altered mental status, diaphoresis, and fevers following a ruptured appendicitis and appendectomy. The patient had growth of Clostridium tertium and Escherichia coli in blood cultures and imaging of the abdomen revealed a large hepatic abscess. Clostridium tertium is an uncommon cause of bacteremia in non-neutropenic patients. There is currently no universally accepted treatment for Clostridium tertium bacteremia. We report successful treatment with ertapenem.